The Effect of Brand Ambassador, Website Quality, and E-WOM on Purchase Decision in Shopee E-commerce - Rina Rahmawati; Rohmat Dwi Jatmiko; Chalimatuz Sa'diyah (Jurnal Maksipreneur, 2022)
This study aims to examine the effect of Brand Ambassador, Website Quality, and Electronic Word of Mouth (E-WOM) partially and simultaneously on Purchase Decisions in Shopee e-commerce. This study uses a quantitative approach with primary data sources collected through questionnaires. The data sample used was 125 respondents from the Management Study Program FEB-UMM (Faculty of Economics and Business, University of Muhammadiyah Malang) as Shopee consumers. The sampling technique is non-probability sampling using the purposive sampling method which gives certain criteria to respondents. In analyzing the data of this study using multiple linear regression analysis tools. The results of this study are Brand Ambassador, Website Quality, and E-WOM have a positive and significant effect on Purchase Decision partially, and simultaneously have a significant effect on Purchase Decisionin Shopee e-commerce.